Development of TAPUBA Puzzle as an Independent Learning Medium for the Periodic System of Elements (Jurnal Inovasi Pendidikan Kimia, 2023)
The material for the periodic system of elements is a chemical material that should be studied independently. However, the lack of media that supports this is a problem. This study aims to develop the TAPUBA puzzle as an independent chemistry learning medium for the periodic table of elements for high school students. This study aims to develop the TAPUBA puzzle as an independent learning media to learn the periodic table. The research used Research and Development (RD) methods. The stages were as follows, analysis, development process, product validation, and assessment stage. Prior to assessment by four chemistry teachers and ten high school students class X science and mathematics program, the TAPUBA puzzle was validated by media and concept experts. The instruments used were validated by an instrument expert. The validation results by media experts and concept experts show that the media is valid in terms of the performance of the media and the material of the periodic system of elements. Teachers’ and students’ assessments showed that the media perform 89,06% and 95,00% in the very good category. The results show that this media is suitable for use in the chemical learning process of the material on the periodic system of elements.